A multicentre study comparing two methods for serum free light chain analysis. (May 2013) - Lock, RJ; Saleem, R; Roberts, EG; Wallage, MJ; Pesce, TJ; Rowbottom, A; Cooper, SJ; McEvoy, ED; Taylor, JL; Basu, S
Background: Serum free light chain analysis is now well established in the investigation of monoclonal gammopathies. In the UK there has, until recently, been a single supplier of kits for such analysis. Recently, a second method using monoclonal antisera was introduced. We have compared the performance of these two kits in four routine laboratories. Method: Samples submitted for routine analysis (327 samples, 258 [79%] from patients with B-cell lymphoproliferative disease) for serum free light chains were tested by both technologies (Freelite, Binding Site and N Latex FLC, Siemens), according to the manufacturers' instructions. Results: Qualitative data were available by both methods on 313 samples for serum free kappa chains and 324 samples for lambda free light chains. We found poor correspondence of 81% for kappa and 74% for lambda. Five percent of samples were significantly discordant in these assays. Conclusions: These assays perform very differently in clinical practice. They cannot be used interchangeably, especially if monitoring patient responses to therapy.